Optimizing the performance of dye-sensitized upconversion nanoparticles. (August 2021) - Zhao, Xiaoyu; Wang, Meifeng; Cai, Zhiwang; Xia, Daoyu; Zhao, Lei; Song, Qingwei; Qin, Yiru; Wei, Wei
Abstract: Upconversion nanoparticles (UCNPs) are promising for bioimaging, sensing, and other applications, but their upconversion (UC) efficiency is far from satisfactory. Organic dye sensitization is considered to be an effective strategy to improve the performance of UCNPs. In this work, we provide direct evidence that organic sensitizer surpasses inorganic sensitizer in sensitization capability. To maximize the performance of dye-sensitized UCNPs, three critical factors, namely different optically inert lanthanide ions, Yb 3+ doping concentration, and particle size, are systemically investigated and optimized. It is found that the optimal Yb 3+ doping concentration and particle size are determined to be 20% and ~19 nm for dye-sensitized UCNPs, while different optically inert lanthanide ions have negligible influence on this system. Importantly, our results suggest that dye sensitization is more favorable for improving the performance of smaller-sized UCNPs. Although ultrasmall UCNPs (<10 nm) are desirable for biomedical applications UCNPs due to their reduced toxicity, they suffer from extremely low UC efficiency and weak brightness. Fortunately, the strategy of dye sensitization turns out to be particularly useful for producing ultrasmall and ultrabright UCNPs, which are desirable for biomedical applications. Graphical abstract: Image 1 Highlights: Organic sensitizer is superior over inorganic sensitizer in sensitization capability. The optimal Yb 3+ doping concentration and particle size are determined to be 20% and ~19 nm for dye-sensitized upconversion nanoparticles, while the doping of different optically inert lanthanide ions has negligible influence on this system. The strategy of dye sensitization is particularly useful for producing ultrasmall and ultrabright upconversion nanoparticles.